Some Exact Solutions of Einstein’s Field Equation’s for Acceleration Free Imperfect Fluid Source: Exploring exact solutions to Einstein's field equations for acceleration-free imperfect fluid sources with shear viscosity (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The research paper provides solution of some exact solution to the Einstein field equation for acceleration free imperfect fluid source with shear viscosity under different conditions. Some physical restriction on the solution have been also discussed.